(untitled) (Research Nepal Journal of Development Studies, 2018)
Cardamom production is a potential cash crop of Kavre district. Many farmers were found to grow cardamom following traditional pattern. Women’s participation in Cardamom production in Kavre is satisfactory and their roles are vital in the farm and market management. To check the status of cardamom production and women’s role in Kavre, the researcher visited the District Agriculture Office and used snowball sampling technique to collect the primary data. For the secondary data, library method has been applied. Although the production and women’s participation are highly encouraging, the farmers are reluctant to invest and produce cardamom at large scale. The study has found that the farmers need the entrepreneurship training, support and empowerment for mass production of cardamom. The future of cardamom production is bright in Kavre. Research Nepal Journal of Development Studies Vol.1(1) 2018 58-65